A "book and Claim"-Approach to account for sustainable aviation fuels in the EU-ETS – Development of a basic concept. (January 2020) - Pechstein, Jan; Bullerdiek, Nils; Kaltschmitt, Martin
Abstract: Since 2012 aviation is included in the EU Emissions Trading Scheme (EU-ETS). The EU-ETS requires emission allowances for CO2 emissions, except if they result from the combustion of Sustainable Aviation Fuels. These fuels are drop-in fuels, i.e., they are fully compatible with conventional aviation turbine fuel, supply infrastructure and aircraft. However, the current EU-ETS regulation to account for the use of sustainable fuels requires their designated /separate logistics to the airport tank farm. This is technically unnecessary, and both environmentally and economically disadvantageous. It thus represents a barrier for the widespread use of Sustainable Aviation Fuels. Against this background, criteria for an advanced accounting methodology are defined and three different chain of custody concepts are evaluated against them. The most suitable solution is based on a book and claim principle, an approach approved by EU institutions in other industries facing similar circumstances. It balances the fuel's technical potential, the administrative burden for the aviation industry and fundamental EU-ETS requirements, like fraud protection. The latter is ensured by the uniform excise tax supervision in the EU. Finally, a holistic layout of a book and claim concept to account for the use of Sustainable Aviation Fuels in the EU-ETS is proposed. Highlights: The EU-ETS accounting methodology for sustainable aviation fuels is inefficient. Similar accounting issues in other sectors are solved using chain of custody concepts. Among three chain of custody concepts evaluated, book and claim is the most suitable. Fraud protection is ensured by pan-EU excise supervision provided by national customs. Future book and claim applications may go beyond the EU-ETS (e.g. mandates, CORSIA).